Beyond Debt: Islamic Experiments in Global Finance - Huang, Wayne (Islamic Studies Review, 2025)
Daromir Rudnyckyj. Beyond Debt: Islamic Experiments in Global Finance. Chicago and London: The University of Chicago Press, 2019. It is remarkable how few scholars of Southeast Asia have thought to look to Islamic finance, and how few scholars of Islamic finance have paid attention to Southeast Asia, for clues as to how global Islamic networks and global finanscapes converge. In part, this two-way oversight reflects the lack of interest in finance capitalism in conventional Southeast Asian studies and the marginal position Southeast Asia continues to occupy in Islamic studies. On this point alone, anthropologist Daromir Rudnyckyj's Beyond Debt: Islamic Experiments in Global Finance, arguably the first ethnography documenting the ongoing experiment of Islamic finance in Malaysia, is a significant contribution.